272Pre-reperfusion metoprolol administration reduces ischemia/reperfusion injury (IRI) through beta1-adrenergic receptor (b1AR) blockade in the circulating cells. (15th July 2014) - Garcia-Prieto, J; Fernandez-Jimenez, R; Sreeramkumar, V; Lunar, I G; Sanz-Rosa, D; Zorita, V; Pizarro, G; Hidalgo, A; Fuster, V; Ibanez, B
Abstract: Background: We have shown that pre-reperfusion metoprolol reduces infarct size in humans (METOCARD-CNIC trial). Preclinical data suggest that this strategy reduces myocardial neutrophil infiltration. Here we evaluated the potential involvement of circulating cells in the cardioprotection afforded by metoprolol. Methods: WT and b1AR-KO mice were subjected to myocardial IRI (45min/24h Ischemia/Reperfusion). Ten minutes before reperfusion, animals were randomized to receive either i.v. metoprolol or vehicle through the femoral vein. In a different experiment, b1AR-KO mice were subjected to lethal irradiation and bone marrow transplant from WT donors. Once fully recovered, animals with more than an 80% engraftment were subjected to IRI and randomized to i.v.metoprolol or vehicle. At the end of the procedure, infarct size was evaluated by TTC/Evans blue staining. Additionally, intravital microscopy was performed in the cremaster muscle of WT and b1AR-KO mice after neutrophil and platelet labeling. Results: Infarct size was 30% smaller in WT animals receiving i.v. metoprolol compared to vehicle. Conversely, metoprolol had no effect on b1KO mice. In b1KO mice transplanted with WT bone marrow, the cardioprotective phenotype of metoprolol was rescued. Metoprolol massively inhibited neutrophil-platelet interactions after TNFa challenging and this effect was absent in b1KO mice. Conclusion: Circulating cells mediates the cardioprotection afforded by i.v. metoprolol.